Radiotherapy of periocular basal cell carcinomas: recurrence rates and treatment with special attention to the medical canthus. Issue 2 (February 1988) - Rodriguez-Sains, R. S.; Robins, P.; Smith, B.; Bosniak, S. L.
Abstract : Basal cell carcinomas of the eyelids, especially those in the medial canthal area, may cause extensive local destruction. Recurrent tumours are more aggressive and become progressively more difficult to treat; this is especially true for postirradiated recurrent, medial canthal, basal cell carcinomas. Tumours in this area should thus be treated by a technique which allows tissue sampling in order to gauge the adequacy of the treatment, with the goal being complete extirpation of the tumour. Excision monitored by frozen section control or Mohs' surgery is our recommendation based on a retrospective analyses of 631 eyelid basal cell carcinomas, half of which were primary tumours and half recurrent.